2021
DOI: 10.1136/bmjopen-2020-038565
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare disparities contribute to missed follow-up visits after cataract surgery in the USA: results from the perioperative care for intraocular lens study

Abstract: ObjectiveTo identify factors that contribute to missed cataract surgery follow-up visits, with an emphasis on socioeconomic and demographic factors.MethodsIn this retrospective cohort study, patients who underwent cataract extraction by phacoemulsification at Massachusetts Eye and Ear between 1 January and 31 December 2014 were reviewed. Second eye cases, remote and international patients, patients with foreign insurance and combined cataract cases were excluded.ResultsA total of 1931 cases were reviewed and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…There was conflicting evidence over follow-up appointment adherence being associated with race and ethnicity. Six studies found that White patients were more likely to follow up with an ophthalmologist than American Indian and Alaska Native, Asian, Black, Hispanic, and Native Hawaiian and Other Pacific Islander patients and patients of unreported race; conversely, 3 studies found no significant association between race and ethnicity and follow-up adherence . Pineles et al reported that White patients were more likely to be diagnosed with eye diseases than patients of other races.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…There was conflicting evidence over follow-up appointment adherence being associated with race and ethnicity. Six studies found that White patients were more likely to follow up with an ophthalmologist than American Indian and Alaska Native, Asian, Black, Hispanic, and Native Hawaiian and Other Pacific Islander patients and patients of unreported race; conversely, 3 studies found no significant association between race and ethnicity and follow-up adherence . Pineles et al reported that White patients were more likely to be diagnosed with eye diseases than patients of other races.…”
Section: Resultsmentioning
confidence: 93%
“…Women were less likely to undergo certain ophthalmic surgical procedures. 55,56 In contrast, 11 studies found no association between sex and/or gender and ophthalmic conditions, 30,34,[57][58][59][60] follow-up adherence, 23,[27][28][29] or access to eye care. 37 Further findings can be found in the eTable in the Supplement.…”
Section: Sex And/or Gendermentioning
confidence: 99%
See 2 more Smart Citations
“… 8 , 9 Healthcare disparities may also contribute to worsened postoperative care in patients who receive cataract surgery. 10 The relationship between SDoH and ophthalmic conditions also is bidirectional; Constantino et al 8 and Brezin et al 11 reported that low visual acuity could in fact be a risk factor for socioeconomic factors such as adverse social outcomes, worsened mental health, and poverty. 12 …”
mentioning
confidence: 99%